Analysis of Replication Intermediates Indicates That Drosophila melanogaster Mitochondrial DNA Replicates by a Strand-Coupled Theta Mechanism - Jõers, Priit (Public Library of Science, 2013)
Mitochondrial DNA synthesis is necessary for the normal function of the organelle and for the eukaryotic organism as a whole. Here we demonstrate, using two-dimensional agarose gel electrophoresis to analyse replication intermediates, that unidirectional, strand-coupled DNA synthesis is the prevalent mode of mtDNA replication in Drosophila melanogaster. Commencing within the single, extended non-coding region (NCR), replication proceeds around the circular genome, manifesting an irregular rate of elongation, and pausing frequently in specific regions. Evidence for a limited contribution of strand-asynchronous DNA synthesis was found in a subset of mtDNA molecules, but confined to the ribosomal RNA gene region, just downstream of the NCR. Our findings imply that strand-coupled replication is widespread amongst metazoans, and should inform future research on mtDNA metabolism in D. melanogaster.